2004
DOI: 10.1111/j.0023-5962.2004.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Bodies: A Hedonic Pricing Model of Avatar Attributes in a Synthetic World

Abstract: Summary This paper explores a unique new source of social valuation: a market for bodies. The internet hosts a number of large synthetic worlds which users can visit by piloting a computer‐generated body, known as an avatar. Avatars can have an asset value, in that users can spend time to increase their skills; these asset values can be directly observed in online markets. Auction data for avatars from the synthetic fantasy world of EverQuest are used here to explore a number of questions involving the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
(10 reference statements)
1
31
1
Order By: Relevance
“…To the best of our knowledge, no research has explicitly addressed this. Since the seminal works by Castronova (2002Castronova ( , 2004, models based on optimal allocation time between leisure and work have been used to explain why players indulge in virtual trade. However, little attention was given to players who live in the virtual world to build their real wealth from there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, no research has explicitly addressed this. Since the seminal works by Castronova (2002Castronova ( , 2004, models based on optimal allocation time between leisure and work have been used to explain why players indulge in virtual trade. However, little attention was given to players who live in the virtual world to build their real wealth from there.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pearce, in her studies of emergent behaviour in online games, has defined these as 'fixed synthetic worlds' for their rigid narratives and theme park 'on the rails' style of game play, and metaverse worlds as 'co-created' worlds where players have an active role in building the world itself (2009: 30-35). Previous research has suggested that in typical game worlds, real world males make up 80 per cent -9 per cent of players' in MMOGs (Castronova 2001;Yee 2003Yee , 2006Seay et al 2004); the ratio is believed to be closer to 50-50 in social virtual worlds (Pearce 2009). One of the aims of this study was to compare attitudes about avatar gender, including cross-gender play, across these two different virtual worlds.…”
Section: Introductionmentioning
confidence: 97%
“…In the domain of digital games, avatars are the virtual representation of the player within a game and have been studied from a variety of perspectives like economics (e.g., [4]) or psychology (e.g., [3]), to name just a few. Whereas in Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%